Embodiments of the Sovereignty of the Republic of Indonesia under the Immigration Control - M Asri Wahyudin (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2018)
The nature of immigration control over the misappropriation of visas and residence permits in Indonesia in the framework of the operationalization of a selective policy of immigration law so that foreigners residing in Indonesia have limitations both in terms of their immigration clearance and their activities. The essence of oversight in order to uphold the sovereignty of the Republic of Indonesia as a jurisdiction, namely: jurisdiction to prescribe, jurisdiction to adjudicate and jurisdiction to enforce. Basically the main objective of foreign control is to protect the people and the sovereignty of the State. Foreigners who do not bring benefits and can jeopardize order should be prevented from entering the territory of Indonesia.